FRACTAL HILBERT SENSOR TO DETECT PARTIAL DISCHARGE ON TRANSFORMER - Sinaga, H. B. H. Sitorus, D. Permata, N. Soedjarwanto, Herman Halomoan (Journal of Engineering and Scientific Research, 2019)
The design of fractal Hilbert sensor is presented in this paper. The sensor is intended to detect partial discharge (PD) in transformer insulation. The fractal Hilbert sensor designed using 4 order fractal and etching on single layer PCB board. The Hilbert fractal type is chosen as this type of sensor can be built on smaller area compare to other types. The sensor overall dimension is limited to 5x5 cm as it is proposed to be use to detect the PD presence in transformer. The sensor sensitivity is tested using a closed type TEM cell. After the sensitivity of the sensor is tested the sensor then applied to detect the PD signals emitted by void PD defect model. The results show the sensor has sensitivity as high as 10 dB. The sensor also has capability to detect the PD signals generated by the PD defect source. The waveforms captured by the sensor show the sensors can capture high frequency pulse generated by the PD source.  Keywords: Partial Discharge (PD), Fractal Hilbert Sensor UHF, Sensor Sensitivity